Analysis of Teacher Difficulties in Online Learning on Mathematics Subjects - Yuyun Nailufar; Safruddin Safruddin; Moh. Irawan Zain (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
The COVID-19 pandemic has had an impact on various fields in the world, without exception in the field of education. This situation causes the change in learning which is usually face-to-face in the classroom to be carried out at home, namely by online learning. During online learning, many students find it difficult to learn mathematics online. This study aims to determine the difficulties of teachers in online learning at SDN 32 Cakranegara in Mathematics. This study is a qualitative descriptive study, the population in this study were all grade III-VI teachers at SDN 32 Cakranegara, the sampling technique used cluster random sampling. The research sample selected was 4 class teachers. The data collection instruments used interview questionnaires, observation sheets, and documentation studies. Data analysis techniques consist of data reduction, data presentation, and Conclusion Drawing/Verification. The results showed that teachers experienced difficulties in online learning, namely: learning planning in the technique of determining learning methods, making learning media and determining 3 types of affective, cognitive and psychomotor assessments. Difficulties in implementing learning in preliminary activities are preparing students psychologically and physically and providing motivation, core activities are observing, asking questions, digging and collecting information and communicating and closing activities on feedback, follow-up and information on further activities. And the difficulty of providing an assessment in applying 3 types of affective assessment on observation, self-assessment, assessment between students and journals. Cognitive on written tests, oral tests and assignments and psychomotor on practice, projects, and portfolios during online learning in Mathematics.